2004
DOI: 10.1002/jsfa.1794
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lipase and/or emulsifier addition on the ileal and faecal nutrient digestibility in growing pigs fed diets containing 4% animal fat

Abstract: Information on the addition of lipase and/or emulsifiers to less digestible or saturated fat sources, such as tallow or other animal fats, used in swine feeding is very limited. Therefore, in a 4 × 4 Latin square design, the effects of adding lipase (0.05% L5, microbial source) and/or an emulsifier (0.3% Lysoforte) on the apparent ileal (AID) and faecal (AFD) digestibility of the main nutrients and fatty acids in particular were studied with four ileal-cannulated growing pigs (female, initial live weight 20 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 38 publications
5
34
2
Order By: Relevance
“…The emulsifying effect of DMG incorporation in the sow's diet not only resulted in improvement of CFAT digestibility, but also improved digestibility of CP and NFE. These findings corroborate with the results of a previously published study on the addition of emulsifying agents to pig feed (Dierick and Decuypere, 2004). Studies on the effects of emulsification of fat sources in piglet feed indicate that the addition of emulsifiers to piglet feed improve nutrient digestibility, resulting in a reduction of feed costs (Jones et al, 1992;Odle et al, 1994).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The emulsifying effect of DMG incorporation in the sow's diet not only resulted in improvement of CFAT digestibility, but also improved digestibility of CP and NFE. These findings corroborate with the results of a previously published study on the addition of emulsifying agents to pig feed (Dierick and Decuypere, 2004). Studies on the effects of emulsification of fat sources in piglet feed indicate that the addition of emulsifiers to piglet feed improve nutrient digestibility, resulting in a reduction of feed costs (Jones et al, 1992;Odle et al, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the results of AFD in this study indicate that DMG may act as an external emulsifier in pig feed (Wieland et al, 1993;Dierick and Decuypere, 2004). The emulsifying effect of DMG incorporation in the sow's diet not only resulted in improvement of CFAT digestibility, but also improved digestibility of CP and NFE.…”
Section: Discussionmentioning
confidence: 57%
“…However, there was no significant influence of AMT supplementation on the ADFI during the first phase in the chickens and piglets, possibly due to the insufficient digestion and absorption of fat in young animals (Dierick and Decuypere, 2004).…”
Section: Discussionmentioning
confidence: 84%
“…Lecithin, as an emulsifier, has been reported to enhance the apparent digestibility of unsaturated fatty acids in lard (Soares and Lopez-Bote, 2002). Dierick and Decuypere (2004) reported that the addition of an emulsifier improved the digestibility of major nutrients, which may reduce the viscosity of the digestive contents and increase the transit of the digesta as well as feed intake (Lázaro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation